A sequência fedathi no ensino da álgebra linear: o caso da noção de base de um espaço vetorial - Fontenele, Francisca Cláudia Fernandes (2013)
This research examined the teaching of concept of base of a vector space according to the premises mediated by Fedathi Sequence during the discipline “Introduction to Algebra” in the course of Engineering of Teleinformatic at Federal University of Ceará. The objective was to determine whether the use of Fedathi Sequence specifically in classes about the concept of base provides resources capable of becoming Meta Lever, allowing students an education based on the reflection on the worked contents. In this sense, the investigation was conducted in the form of case study, having as subject the teacher of discipline, which allowed the observation during his classes and planning, as well as having granted an interview. The results indicated that the Fedathi Sequence favored the use of resources that could become Meta Lever for students, being decisive in mediating the teacher, once the teacher behavior to use it in the classroom motivates students to reflection. We consider theories ML and FS, in this research, are complementary, and therefore we indicate that the teacher know such tools and their potential for use in teaching of concept of base, awakening the teacher an awareness of the role of mediation suggested by Fedathi Sequence.